2014
DOI: 10.7554/elife.03581
|View full text |Cite
|
Sign up to set email alerts
|

GluN2B-containing NMDA receptors regulate depression-like behavior and are critical for the rapid antidepressant actions of ketamine

Abstract: A single, low dose of the NMDA receptor antagonist ketamine produces rapid antidepressant actions in treatment-resistant depressed patients. Understanding the cellular mechanisms underlying this will lead to new therapies for treating major depression. NMDARs are heteromultimeric complexes formed through association of two GluN1 and two GluN2 subunits. We show that in vivo deletion of GluN2B, only from principal cortical neurons, mimics and occludes ketamine's actions on depression-like behavior and excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
220
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(246 citation statements)
references
References 84 publications
(136 reference statements)
14
220
1
Order By: Relevance
“…For example, deletion of GluN2B in principal cortical neurons mimics and occludes the actions of ketamine on behavior, glutamatergic synaptic transmission and protein synthesis. 86 Knockdown of GluN2B in the bed nucleus of the stria terminalis also mimics the affective effect of ketamine 87 and deletion of GluA1 in glutamatergic neurons during adolescence induces behavioral alterations that resemble schizophrenia-like abnormalities but not depression-or anxiety-like alterations. 88,89 Knock-in mice in which Ser 845 -GluA1 is replaced by alanine demonstrate loss of ketamineinduced synaptic potentiation in the hippocampus and impaired behavioral improvement induced by ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, deletion of GluN2B in principal cortical neurons mimics and occludes the actions of ketamine on behavior, glutamatergic synaptic transmission and protein synthesis. 86 Knockdown of GluN2B in the bed nucleus of the stria terminalis also mimics the affective effect of ketamine 87 and deletion of GluA1 in glutamatergic neurons during adolescence induces behavioral alterations that resemble schizophrenia-like abnormalities but not depression-or anxiety-like alterations. 88,89 Knock-in mice in which Ser 845 -GluA1 is replaced by alanine demonstrate loss of ketamineinduced synaptic potentiation in the hippocampus and impaired behavioral improvement induced by ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…94 Ketamine was shown to increase BDNF in the hippocampus but this effect was not sustained after 24 h. 20 Our results do not allow us to determine if ketamine alters the levels of BDNF in the NAc and VTA, because the levels of this growth factor were unaltered 24 h after the injection, which might indicate that BDNF levels have already returned to baseline levels both in the NAc and VTA. Enhanced AMPAR function, as demonstrated by, for example, enhanced AMPA/NMDA ratio, increased glutamatergic synaptic transmission or increased phosphorylation of GluA1, 5,7,38,86,95 was suggested to mediate synaptic plasticity underlying the antidepressant effects of ketamine and (2R,6R)-HNK. These observations were made in the hippocampus or prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as an adaptor protein, it has been shown that Homer functions as ligand and directly modulates the Ca 2+ release gain via ryanodine receptor (Feng et al, 2002). The long Homer1b/c links metabotropic glutamate receptors (mGluR1 and mGluR5) with NMDA receptors (Perroy et al, 2008;Bertaso et al, 2010) and many proteins involved in Ca 2+ signaling Feng et al, 2002;Hwang et al, 2003;Yuan et al, 2003), all of which have been implicated in the pathophysiology of mood disorders (Galeotti et al, 2008a,b;Krystal et al, 2010;Miller et al, 2014;Newell and Matosin, 2014). Therefore, abnormal clustering and declustering of Homer1b/c may provide an important mechanism that underlies the pathophysiological processes of depression (Szumlinski et al, 2006;Luo et al, 2012).…”
Section: Homer1 Proteinsmentioning
confidence: 99%
“…However, how Homer1a mediates antidepressant effects is currently unknown. As the key scaffolding molecule at the PSD, constitutively expressed long Homers form a polymeric network complexes linking mGluR5 with NMDA receptors and various proteins involved in Ca 2+ homeostasis Feng et al, 2002;Hwang et al, 2003;Yuan et al, 2003;Perroy et al, 2008;Bertaso et al, 2010), which have been all implicated in the pathophysiology and treatment of depression (Galeotti et al, 2008a,b;Krystal et al, 2010;Miller et al, 2014;Newell and Matosin, 2014). The induction of Homer1a, which acts as a dominant negative protein and declusters long Homer complexes, might serve as a therapeutic method in depression to modulate activity of the target proteins.…”
Section: Conclusion and Future Prospectivesmentioning
confidence: 99%
“…The summary of pharmacodynamics is (1) blockade of interneuronal NMDA receptors, (2) disinhibition of pyramidal cells leading to a glutamate surge, (3) activation of the AMPA receptors, (4) blockade of the excitotoxic extrasynaptic NMDA receptors, (5) activation of synaptogenic intracellular signaling and brain-derived neurotropic factor pathways, and (6) stimulation of the mammalian target of rapamycin. [17][18][19][20][21] In another study, Salat et al studied the antidepressant effect of ketamine, norketamine and dehydro ketamine using the forced swim test. They concluded that ketamine (10 mg/kg) and norketamine (50 mg/kg) reduced immobility time whereas dehydro norketamine did not.…”
Section: Discussionmentioning
confidence: 99%